2017
DOI: 10.1021/acs.langmuir.7b02710
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Nanocrystal Superlattice Nucleation and Growth

Abstract: Colloidal dodecene-passivated silicon (Si) nanocrystals were dispersed in hexane or chloroform and deposited onto substrates as face-centered cubic superlattices by slowly evaporating the solvent. The uniformity of the nanocrystals enables extended order; however, the solvent and the evaporation protocol significantly influence the self-assembly process, determining the morphology of the films, the extent of order, and the superlattice orientation on the substrate. Chloroform yielded superlattices with step-fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 72 publications
0
11
0
Order By: Relevance
“…Small- and wide-angle scattered photons were collected with a PILATUS3 R 300K detector with 487 × 619 pixels and a pixel size of 172 μm × 172 μm positioned at the appropriate distances from the sample (134 mm for GIWAXS and 1084 mm for GISAXS). FIT2D software (version: 12_077_i686_WXP) was used to process the patterns. , …”
Section: Methodsmentioning
confidence: 99%
“…Small- and wide-angle scattered photons were collected with a PILATUS3 R 300K detector with 487 × 619 pixels and a pixel size of 172 μm × 172 μm positioned at the appropriate distances from the sample (134 mm for GIWAXS and 1084 mm for GISAXS). FIT2D software (version: 12_077_i686_WXP) was used to process the patterns. , …”
Section: Methodsmentioning
confidence: 99%
“…In the past few years, many research groups have reported on assembly techniques of micrometer-sized mesocrystals of platinum, magnetite, lead sulfide, and silver, among other materials. , They have shown remarkable structures of mesocrystals, which are perfectly regular and feature well-defined facets, like “classical” crystals. Commonly, nanocrystals are assembled into mesocrystals either via “drying mediated assembly methods” or via the “gas phase diffusion technique”. ,,,, Often, the structure of these assemblies is characterized incompletely, with the main emphasis on the study of explicit properties or specific applications of mesocrystals. ,,, Nevertheless, investigations with a combination of small- and wide-angle X-ray scattering techniques (SAXS and WAXS) as well as advanced microscopy techniques allow a full structural analysis of self-assembled superstructures based on nanoparticles of different compositions and shapes. ,,,,,, The recently developed angular X-ray cross-correlation analysis (AXCCA) method allows the determination of the superlattice distortion and relative orientation of nanoparticles in mesocrystals with high precision. Similarly, great effort is put on how these crystals nucleate and grow and how the kinetics influence the nonclassical crystallization of mesocrystals. ,, Furthermore, there are many interesting results on how growth conditions can impact the final structure of mesocrystalline films. Accordingly, different superlattice structures can be obtained by solvent evaporation from dispersions with different dispersion agents as well as from nanoparticles stabilized by different ligands. , However, an understanding of the morphogenesis of macroscopic mesocrystals is still essentially lacking. Specifically, the exact parameters which influence the crystal structure and morphology, including packing arrangement and orientational order, remain largely unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Nanocrystal Superlattice Assembly. Superlattices of MAPI nanocrystals were prepared by solvent evaporation on TEM grids for TEM imaging or Si wafer substrates for scanning electron microscopy (SEM), X-ray diffraction (XRD), and GISAXS/GIWAXS using the methods of Guillaussier et al 51 It was necessary to store the nanocrystals as concentrated dispersions in hexane. The nanocrystals were found to degrade in either chloroform or toluene.…”
Section: ■ Introductionmentioning
confidence: 99%